Contamination du lac Saint-Pierre (fleuve Saint-Laurent) par certains polluants organiques et inorganiques - C. Langlois; H. Sloterdijk (Revue des sciences de l'eau, 2005)
As part of a monitoring program on pollutants dispersion in the St. Lawrence river, a study was conducted in 1986 on the fate and pathways of toxic substances in Lake St. Pierre. This enlargement of the St. Lawrence drains the Montreal metropolitan area and the international great lakes region. Water, sediments and fish were collected and analyzed. Water was sampled following the conventional method (1 l) or passed through an XAD-2 resin column (70 l of centrifuged water). Suspended sediments were collected by centrifuging 2000 l of water. Bottom sediments were collected by retaining the top layer of a grab sample taken using an Eckman dredge. Young-of-the-year forage fishes (Spottail Shiner and Yellow Perch) were captured using a seine whereas adult fishes (Northern Pike, Walleye, Brown Bullhead, Yellow Perch, White Sucker, Bowfin and Burbot) were captured using hoop-nets and gill-nets. All samples were analyzed for metals, organochlorine pesticides, PCBs, PAHs and chlorobenzenes. Fishes were analyzed as homogenate of whole individuals (young-of-the-year and adult) and as homogenate of fish flesh. Results indicate that the level of contamination by toxic chemicals is highly significant. The major contaminants found in the different media are arsenic, mercury, iron, PCBs and various derivatives of DDT. The concentration frequently exceeds the guidelines suggested for mercury in fish flesh, iron in water and sediments and PCBs in most compartments analysed. Several organochlorine pesticides have been detected in water using Large Volume Sampling technique. This technique allows estimation of background concentration and annual mass balance for specific pollutants. Whole fishes and Burbot's livers are good indicators of the presence and concentration range of bioaccumulating toxic substances. Bottom sediments and juvenile fishes are good indicators of spatial distribution of toxic chemicals in the lake. PCB's highest concentrations are found in adult whole fish samples (mean of 1030 µg/kg). Bottom sediments ...